2012
DOI: 10.1002/lary.22397
|View full text |Cite
|
Sign up to set email alerts
|

Current dysphonia trends in patients over the age of 65: Is vocal atrophy becoming more prevalent?

Abstract: As the number of people in the over 65-year-old age bracket increases, so do the number of geriatric referrals. Although diagnostic trends remain the same, vocal atrophy is becoming more prevalent, with a large number of patients seeking intervention. This will likely result in an increased need for health resources in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
58
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 13 publications
(17 reference statements)
0
58
0
4
Order By: Relevance
“…A large retrospective study identified vocal fold (VF) atrophy as the most prevalent finding in an elderly cohort [9]. The noticeable glottal gap and VF bowing are the most prominent video-laryngoscopic findings in these patients and are related to the atrophy of the laryngeal mucosa and the subjacent thyroarytenoid muscle (TAM) [10].…”
Section: Introductionmentioning
confidence: 99%
“…A large retrospective study identified vocal fold (VF) atrophy as the most prevalent finding in an elderly cohort [9]. The noticeable glottal gap and VF bowing are the most prominent video-laryngoscopic findings in these patients and are related to the atrophy of the laryngeal mucosa and the subjacent thyroarytenoid muscle (TAM) [10].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 This variability is likely due to differences in the geriatric subpopulation assessed, definitions of dysphonia, and methodologies used to identify dysphonia. Understanding the prevalence of dysphonia in large segments of the geriatric population is important to improve identification and interventions in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reporting geriatric incidence of dysphonia have surveyed ambulatory outpatients and senior community residents as a proxy for all geriatric individuals, which excludes an important subset of individuals, residents in assisted living and nursing facilities. 10,11 We hypothesized that frailty is positively correlated with dysphonia in geriatric populations. Additional aims of our study were to identify the prevalence of dysphonia in two previously unstudied groups, assisted living residents and nursing home residents and to evaluate the utility of the Vulnerable Elders Survey-13 (VES-13) to otolaryngology research protocols.…”
Section: Introductionmentioning
confidence: 99%
“…1 Within the aging population, the incidence of vocal disorders is estimated to be between 12% and 35%. 2 In a series reported by Davids et al, 25% of patients over age 65 years presenting with a voice complaint were found to have vocal fold atrophy (presbylarynges), where the hallmark physical signs are vocal fold bowing with an increased glottic gap and prominent vocal processes. 2 The epithelial and lamina propria covering of the vocal folds begin to exhibit changes due to aging.…”
mentioning
confidence: 98%
“…2 In a series reported by Davids et al, 25% of patients over age 65 years presenting with a voice complaint were found to have vocal fold atrophy (presbylarynges), where the hallmark physical signs are vocal fold bowing with an increased glottic gap and prominent vocal processes. 2 The epithelial and lamina propria covering of the vocal folds begin to exhibit changes due to aging. In older adults, the collagen of the vocal folds lose their "wicker basket" type of organization, which leads to more disarrayed segments throughout all the layers of the lamina propria, and there is also a loss of hyaluronic acid and elastic fibers.…”
mentioning
confidence: 98%